Effects of solid solution and aging treatment on the microstructure evolution of Ti2AlNb alloy - Zhao Shang; Huijun Niu; Ai Wang; Tuanying Lei; Gang Liu; Lisheng Zhong (Journal of Materials Research and Technology, 2024)
The effects of solid solution temperature, aging temperature and aging cooling rate on the microstructure evolution of forged Ti-22.5Al-24.7Nb (at. %) alloy were investigated. With the increasing solid solution temperature, the number of equiaxed microstructure first increases and then decreases, reaching the maximum at 900 °C. Lamellar microstructure solubilizes in the matrix or gradually becomes coarser and shorter, and transforms into equiaxed microstructure. When the solution temperature is 1000 °C, equiaxed α2 phase gradually changes to be lath-shaped and concave. During the aging process, some α2 phase transforms into O phase, and the aging temperature affects the shape of equiaxed microstructure and the spacing between the needle-like microstructure. With the increasing aging temperature, the number of equiaxed microstructure increases linearly, and the proportion of fine secondary O phase decreases while the thickness increases. The lamellar morphology of O phase can be retained at a faster cooling rate, while a portion of lamellar O phase is converted to the B2 phase after furnace cooling. Through heat treatment, the volume fraction and the size of lamellar O phase could be well controlled.